Проектування сайту візитки для інстаграм магазину - Лимар, В. Ю. (ХНУРЕ, 2021)
The study considers the process of designing an electronic multimedia publication, in the case of a business card site for Instagram stores, as well as technologies for its development, manufacture and design . The study examines current trends, namely: adaptation for mobile devices (because the site is planned for Instagram store, this is the most important criterion), download speed and performance, minimalism, personalization of illustrated design, CSS animation, adaptive design, color gradient design, typographic design site.
Keywords: сайт візитки; візитка